Prevalence of Allergic Rhinitis based on World Health Organization (ARIA-WHO) questionnaire among Batch 2010 Students of the Faculty of Medicine Universitas Padjadjaran - Fauzi Fauzi; Melati Sudiro; Bony Wiem Lestari (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Allergic rhinitis (AR) is a common disease affecting 5–45% of Asian population. Although it is not a life-threatening disease, AR significantly hampers the quality of life of the sufferers. The prevalence of AR among adults in Indonesia is still unknown. This study aimed to measure the prevalence of AR among batch 2010 students of the Faculty of Medicine, Universitas Padjadjaran.Methods: A cross-sectional study was conducted during June–October 2013 involving Indonesian class batch 2010 students of the Faculty of Medicine, Universitas Padjadjaran. The sampling was performed usingtotal sampling approach. The measurement tool used in this study was the Indonesian translation of the Allergic Rhinitis and its Impact on Asthma-World Health Organization (ARIA-WHO) questionnairee. Thosewho were aware of being diagnosed with AR or had two/more AR defining symptoms in the questionnaire form were considered to have AR. The statistical analysis was conducted by calculating frequencies.Results: A total of 207 questionnaire forms were adequately filled out and returned. Based on the questionnaire, the prevalence rate of AR was 38.2%. Of the 79 AR cases, 66% cases involved females. In addition, 54% of the the AR cases have a parental history of allergic diseases. Nasal obstruction and itchy nose were the most frequent symptoms (90%), followed by rhinorrhea (89%), sneezing (82%), and eye symptoms (62%). Based on the duration, the majority fell into the intermittent group (91%); whereas basedon severity, the majority was in the moderate-severe group (71%).Conclusions: The prevalence rate of AR obtained in this study is within the estimated range of Asian population. [AMJ.2015;2(4):620–5] DOI: 10.15850/amj.v2n4.658